Influência de filmes finos na sensibilidade de redes de bragg corroídas: uma análise numérica - Pavellegini, Gisele Mayara Randon (2021)
In this work, the effect of thin films on the sensitivity of corroded Bragg grid is analyzed. It was possible to carry out a study of the influence of the refractive index of the film and its thickness, on the effective refractive index of the modes propagated within the fiber. In addition, the distribution of the electric field within the fiber was investigated by proposing a model for the response of the device. For this, a numerical model based on the finite element method was used. This method is very suitable for solving problems where interactions with the neighborhood occur as well as for stability and accuracy. The results obtained point to a significant non-linear increase in sensitivity when the film is covered with thin films with higher refractive index and, similarly, for devices covered with films of greater thickness. The increase in sensitivity occurs due to the greater distribution of the evanescent field proportional to the increase, both in the refractive index of the film and in its thickness. The study of the parameters A, B, C and k the proposition of an equation for the grid response taking into account the refractive index of the film and its thickness.